Pancreatic cancer treatment with targeted therapies: are we there yet - Nwaefulu, O. Ngozi; Sagineedu, S. Rao; Islam, M. Kaisarul; Stanslas, J. (Verduci International, 2022)
Objective: Pancreatic cancer (PaCa) is a disease that is extremely difficult to treat and is associated with a high fatality rate. The majority of patients present to hospitals with metastatic or end-stage cancer, making the ultimate cure impossible. End-stage PaCa has no specific treatment, though surgery, irradiation, and chemotherapy can help patients live longer. Consequently, it is vital to accumulate all information on potential targeted therapies for this cancer into a single report. Materials and methods: This review has been compiled using relevant keywords and a thorough web search utilising PubMed, ScienceDirect, GoogleScholar, Scopus, MEDLINE, and SpringerLink. Results: Conventional medicines that target various biological processes have a significant negative impact on normal cells. As a result, targeted therapies are required, which include the use of small-molecule inhibitors and monoclonal antibodies to target cancer cell surface receptors, growth factors, and other proteins involved in disease progression. In this review, we summarize the known targeted PaCa therapies, which include inhibitors of the KRAS, mTOR, and PI3K/AKT signaling pathways, as well as PARP, hedgehog, EGFR/ErbB, and TGF-β signaling pathways, along with inhibitors of the neurotrophic tropomyosin receptor kinase (NTRK). Conclusions: An adequate understanding of PaCa pathogenesis and the adoption of tailored medicines can increase patients’ overall survival. We believe targeted therapy can help patients with PaCa to have a better prognosis. As such, more research is needed to find appropriate biomarkers to aid in early tumor diagnosis and to discover novel prospective therapeutics based on the drugs listed in this article.